A Case of Vogt-Koyanagi-Harada Disease-Like Uveitis Induced by Nivolumab and Ipilimumab Combination Therapy - Keisuke Minami (Karger Publishers, 2021)
Nivolumab and ipilimumab are widely used immune checkpoint inhibitors (ICPIs) for the treatment of metastatic melanoma. ICPIs cause an array of side effects called immune-related adverse events (IRAEs) due to activation of an immune response. ICPI-uveitis can cause irreversible vision loss if untreated. There are few reports of recurrent Vogt-Koyanagi-Harada (VKH) disease-like uveitis induced by nivolumab and ipilimumab. We report a case of VKH disease-like uveitis recurrence after resuming ICPIs. A 73-year-old man with advanced melanoma was referred to our clinic with visual loss 25 days after starting nivolumab/ipilimumab. His corrected visual acuity was 0.5 in the right eye and 0.02 in the left eye. Enhanced-depth imaging optical coherence tomography (EDI-OCT) showed marked choroid thickening. The patient was diagnosed with VKH disease-like uveitis due to IRAEs. Subtenon injection of triamcinolone acetonide was performed, and nivolumab/ipilimumab was suspended, but serous retinal detachment (SRD) markedly worsened and choroidal detachment appeared. With 2 courses of steroid pulse therapy and oral steroids, SRD disappeared, and corrected visual acuity recovered in both eyes. Five months after the first injection, exacerbation of melanoma was observed, and nivolumab and oral steroids were restarted. Six weeks later, an increase in choroidal thickness was observed with EDI-OCT and diagnosed as a recurrence of VKH disease-like uveitis. Monitoring for the recurrence of VKH disease-like uveitis during the administration of ICPIs, even after uveitis is treated, is essential. Assessment of choroidal thickness with EDI-OCT may be useful for detecting early signs of VKH disease-like uveitis.